Engaging urban research in policy making Towards equitable economic growth. A partnership between Cities Alliance, AURI, REDEUS_LAC and N-AERUS - Alfaro d'Alençon, Paola; Boanada-Fuchs, Anthony; Greene, Margarita; Krishnamurthy, Sukanya; Michelutti, Enrico; Moretto, Luisa; Smit, Warren (Universitätsverlag der Technischen Universität Berlin, 2023)
Cities are considered "engines of economic growth," yet many cities in the global South struggle to increase productivity and provide significant economic opportunities for their growing populations. There is a need to deepen the knowledge on the links between public goods and services and equitable economic growth and how to support such processes, in policy and strategic terms, locally and globally. Against this background, this publication developed in the collaboration between Cities Alliance's Equitable Economic Growth Cities Campaign initiative and three international research networks N-AERUS, AURI, REDEUS_LAC. The research explores how the interface between urban research and policymaking can be redefined to ensure that public goods and services foster equitable growth. It reveals a richness of practices that provide a broad and lasting positive impact in terms of equitable economic growth in urban development. One of them shows that collaborative efforts between academia, policy makers, communities, and practitioners can play a crucial role in enriching these debates and processes.